WHO Safer Surgery checklist compliance amongst paediatric emergency plastic surgery patients in an UK hospital - Keijzer, Welmoed W. (Ann Med Surg (Lond), 2017)
INTRODUCTION: The WHO Safer Surgery checklist has become an important component of perioperative safety. Our objective, was to determine the compliance of completing the checklist for paediatric emergency plastic surgery patients at our unit. METHODS: An initial baseline was performed with 70 patients over two months at our unit. Following this, we raised awareness at an audit meeting and closed the audit loop using 80 patients over two months. The audit is reported in line with SQUIRE 2.0 criteria. RESULTS: Initial compliance was 88% overall and this increased to 91% post-intervention. Compliance with the individual stages in both cycles was for sign-in: 85%–86%, for time-out 92%–98% and for sign-out 86%–89%. Around one in four checklists were not scanned in both periods. CONCLUSION: This audit showed a high overall level of compliance in the checklists that were scanned and available for scrutiny. We have identified the areas that most need improvement and suggest ways for doing so.